DAMPAK KEBIJAKAN KUALITAS SUMBER DAYA MANUSIA PEGAWAI NEGERI SIPIL DILINGUNGAN PEMERINTAH KECAMATAN SIAU TIMUR KABUPATEN KEPULAUAN SITARO (Suatu Studi Di Kantor Kecamatan Siau Timur) - Masambe, Stein; Kiyai, Burhanuddin; Plangiten, Novva (JURNAL ADMINISTRASI PUBLIK, 2016)
ABSTRACT: This study is based on the results of the initial observation that the performance of employeesgovernment environments Eastern District of Siau indicated relatively low. This condition is presumablyrelated to the implementation of policies not optimal development of human resources quality civil servantsin the region. Thus, this study aims to: (1) Examine the impact of the quality of human resource developmentpolicy environment of government civil servants Eastern District of Siau Island District Sitaro. (2) to analyzedifferences in the performance of employees government environments Eastern District of Siau IslandDistrict Sitaro between before and after participating in education and training (Training).This research applies descriptive and quantitative approach combined with a qualitative approach, thesample of respondents purposively set as many as 44 employees. After analyzing the data collected byapplying the product moment correlation technique and simple linear resgresi.The results of data analysis showed that (1). The average implementation of the development policy ofhuman resource quality of civil servants and the gains of government employees districts Siau Timur, bothare in the category of "medium" or not achieve optimal results. (2) Policy development of quality humanresources dilingkingan government civil servants Eastern District of Siau positive and significant impact onemployee performance improvement.The conclusions that can be drawn from this research is that an employee who has been following thedevelopment program through education and training (training) showed a much higher performance thanbefore following the employee development program. Advice can be given is conveyed to the government ofRegency Sitaro for more intensive follow-include civil servants, either at the district or sub-district / villagein educational activities and training, and much needed concrete efforts of the local government districtSitaro in the form of rotation, transfer, training in the workplace and others.Keywords: Policy penghembangan HR, employee performance